Analisis Tingkat Kepuasan Calon Penumpang Kereta Api Terhadap Penerapan Protokol Kesehatan Di Stasiun Nganjuk Pada Masa Pandemi Covid – 19 - Kurniawan, Safrudin; Handoko, Handoko; Wiarco, Yuwono (Politeknik Perkeretaapian Indonesia Madiun, 2021)
Nganjuk Station is a class 1 (one) station located in Mangundikaran, Nganjuk city, included in the 7 Madiun Operational Area. During the Covid-19 pandemic at Nganjuk Station, health protocols were applied to prevent or reduce the transmission of the corona virus following the regulation of the Minister of Transportation No. PM 18 of 2020. This study aims to determine the level of satisfaction with the application of health protocols at Nganjuk Station during the Covid-19 pandemic and what attributes must be maintained or improved. This study uses the Customer Satisfaction Index (CSI) in calculating how much the passenger's perception of satisfaction with the application of health protocols is, and uses the IPA (Importance Performances Analysis) method to identify which attributes are very important and need improvement for passengers to improve the implementation of health protocols in Indonesia. Nganjuk Station. From the results of this study, the level of satisfaction of prospective passengers with the application of health protocols is 84.97%, which is included in the Very Satisfied category.